Indicadores de desempenho técnico-tático e biomarcadores em atletas de categorias de base no voleibol de praia - Costa, Yago Pessoa da (2018)
In sport with net, such as beach volleyball, technical-tactical performance is fundamental for success; however, the large number of variables hinders generalization. Moreover, success in the game should not be understood only by the technical-tactical performance and may be influenced by hormones. Thus, testosterone and cortisol have a lot of attention, the relationship with power production, social relationships and stress. In this way, the aim was to analyze the performance through technical-tactical and biological indicators in young beach volleyball athletes. Sixteen athletes, male, with a mean age of 17 ± 2,44 years participated in the study. Each pair was submitted to a game, following the official rules, being evaluated as to the performance in the game and the answers for testosterone, cortisol and ratio T:C, verified by the saliva by Elisa. Data were presented on average, standard deviation and frequency distribution, according to the need, as well as compared by student t test Independent, Anova one and two-way, with post hoc sidak. Besides that, the Pearson correlation was used, having significance of p≤ 0,05 for all the tests. Regarding technical-tactical performance, the post-defense attack proved to be the main performance indicator, followed by the attack. As for the biomarkers, there was no difference in training for the day of competition for any of the variables (p≤ 0,05). In addition, no significant difference was found between the winning and losing athletes but cortisol correlated negatively to the performance of the attack (r = -0,542, p = 0,030; moderate) the ratio T:C at the beginning of the game and at the end of the first set was positively correlated (r= 0,646; p= 0,007; r= 0,612; p= 0,012, respectively; moderate). Cortisol is elevated because of the game; also, the technical-tactical performance of serve and the attack improve because of testosterone, but in conditions of lower cortisol. Additionally, cortisol impairs the attack.